2015
DOI: 10.5588/ijtld.14.0945
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma inducible protein-10 in the diagnosis of paediatric tuberculosis infection in a low TB incidence country

Abstract: The IP-10 assay could be useful in improving the diagnosis of LTBI in patients aged <5 years in combination with existing interferon-gamma release assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
2
15
1
Order By: Relevance
“…Seven (58%) studies were performed in low-burden countries, where the TB incidence was 4.4e77 per 100 000 individuals [14,18,21e25]. Two (17%) studies only included children [22,27], three (25%) studies included both children and adults [18,20,21], six (50%) studies only included adults [14,19,23e25,28], and one (8%) study did not report ages [26]. Nine studies reported BCG vaccination statuses.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…Seven (58%) studies were performed in low-burden countries, where the TB incidence was 4.4e77 per 100 000 individuals [14,18,21e25]. Two (17%) studies only included children [22,27], three (25%) studies included both children and adults [18,20,21], six (50%) studies only included adults [14,19,23e25,28], and one (8%) study did not report ages [26]. Nine studies reported BCG vaccination statuses.…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%
“…After database searching and selection criterial, our systematic review and meta-analysis enrolled 14 studies examining the ability of cytokine production to distinguish between active TB and LTBI [16,[28][29][30][31][32][33][34][35][36][37][38][39][40]. Specifically, 8 studies with 11 independent data detected IL-2 levels [29,[31][32][33][34][38][39][40], 8 studies for IP-10 representing 10 independent data [28,30,[35][36][37][38][39][40], 6 studies for IFN-γ representing 8 independent data [28,29,33,[38][39][40], 3 studies for IL-13 representing 4 independent data [28,29,38]. The detection of IL-5, IL-10 and TNF-α were available from 3 independent studies.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, no significant difference was found between active TB, LTBI, infected group and control group in terms of unstimulated plasma IP-10 levels. 22 In another study in the pediatric age group, in which both stimulated and nonstimulated plasma IP-10 levels were evaluated, nonstimulated plasma IP-10 levels were found to be successful in the differentiation of active and LTBI groups, but this differentiation could not be made with stimulated plasma IP-10 levels. 10 In our study, plasma IP-10 levels of our "infected group" consisting of the combination of active TB and LTBI groups were found to be significantly higher than the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Also, while there are studies showing that IP-10 can differentiate between LTBI and active TB, other studies, like ours, have found that it is not effective. 6,19,22 In the study by Wang et al conducted on adults, it was possible to differentiate between unstimulated plasma IP-10 levels from active TB and LTBI; however, this was not possible with stimulated samples. 23 La Manna et al found in their study that the stimulated plasma IP-10 was significantly higher than the nonstimulated plasma IP-10 in differentiating active TB and LTBI.…”
Section: Discussionmentioning
confidence: 99%